HUBUNGAN POLA ASUH ORANG TUA DENGAN KECEMASAN PADA REMAJA SMPN DI KECAMATAN BANJARSARI CIAMIS - , Ima Sukmawati; , Prof. dr. Djaswadi Dasuki, MPH., Sp. OG, Ph. D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Nowadays, anxiety in adolescents continues to increase around 25% and will continue to grow because the symptoms are not recognized. Anxiety is influenced by biological, psychoanalytic, psychosocial, and environmental factors. Of environmental factors, the factor that increases the anxiety is parenting consisting of authoritative, permissive, and democratic styles. Anxiety in adolescents if untreated will lead to poor emotional development, academic impairment, social phobia, and low self esteem. Anxiety in adolescents is influenced by gender and psychosocial stressors. Objectives: To determine the relationship of parenting to anxiety in adolescents among students of SMPN in Banjarsari Sub-District, Ciamis and to determine the relationship of psychosocial stressors and gender to anxiety in adolescents among students of SMPN in Banjarsari Sub-District Methods: This was an observational study with a quantitative method using crosssectional design study, supported by a qualitative method using interview. Study sample was 220 people chosen with cluster sampling at four public junior high schools (SMPN) in Banjarsari Sub-District, Ciamis. Instruments used were the Parental Authority Questionnaire (PAQ) to measure parenting, Lifestyle Assessment Inventory to measure psychosocial stressors and Taylor Manifest Anxiety Scale (TMAS) to measure anxiety. Bivariabel analysis used one way Analysis of Variance (ANOVA) and correlation test and multivariable analysis used linear regression. Results: Analysis of correlation and regression tests showed a significant relationship between anxiety in adolescents and mother's authoritarian parenting pattern (p <0.05). Bivariabel analysis was significant relationship between gender and anxiety in which the score of adolescent girls was higher than that of adolescent boys. Meanwhile, psychosocial stressors in young adolescents with anxiety there is no significant relationship. The qualitative result through interview that adolescents were more close to mother than father, between father and adolescents tended less of communication because father held the power in making decision, while adolescents did not give any chance to convey their thought or ideas Conclusion: Anxiety in adolescents among students of SMPN in Banjarsari Sub- District had a relationship with motherâs authoritarian parenting pattern and gender of adolescents.